Computational repurposing of 1,2,4-triazole-based Schiff bases as anticancer candidates: target-specific docking, DFT reactivity descriptors, and ADMET profiling - Bhandari, Kishor; Shakya, Bhushan (BIBECHANA, 2026)
The epidermal growth factor receptor (EGFR) has become a key target for most researchers involved in the field of anticancer drug discovery due to its role in tumor growth and progression. A series of previously reported Schiff bases of 1,2,4-triazole (T1-T8), in this study, were chosen to evaluate their potential to inhibit EGFR by applying a number of in silico techniques. To perform molecular docking experiment, Kinase domain of EGFR (PDB ID 1M17) was used.  Among the selected compounds, T2 and T5 were found to possess the most favorable binding potential with strong binding affinity of -7.236 and -7.213 Kcal/mol, respectively. They formed stable hydrogen bond and π-type interaction with important residues including MET769, GLN767, THR830, and LYS721. The validation of docking procedure confirmed the reliability of the adopted computational methodology. Quantum chemical (DFT) calculations were used to investigate the electronic properties and behaviors of the compounds. The analysis reported the balanced reactivity and stability of the studied compounds that could be responsible for the interaction with the receptor. The molecular electrostatic potential (MEP) maps also confirmed the results obtained by supporting the presence of electron-rich and electron-deficient regions. In addition, in silico ADMET studies showed that the pharmacokinetic properties of the compounds are favorable. Predicted oral absorption and drug-likeness were favorable, while blood–brain barrier penetration was limited for the majority of the derivatives. Toxicity predictions indicated a generally manageable safety profile, with compounds T5–T7 showing particularly promising characteristics. Collectively, these findings suggest that the selected 1,2,4-triazole Schiff bases represent promising scaffolds for further optimization as EGFR-targeted anticancer agents.